2020
DOI: 10.1186/s12955-020-1273-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in adolescents with persistent pain and the mediating role of self-efficacy: a cross-sectional study

Abstract: Background: Persistent pain has a high prevalence among adolescents. Pain has been shown to reduce all aspects of the adolescent's health-related quality of life (HRQOL). In adult patients with pain, self-efficacy has been shown to mediate the relationship between pain intensity, disability and depression. However, little is known about whether self-efficacy acts as a mediating variable in the relationship between persistent pain and HRQOL sub-scale scores in a school-based population of adolescents. Objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 70 publications
(87 reference statements)
2
25
1
1
Order By: Relevance
“…SE is a positive phenomenon, and it is particularly relevant from a health promotion perspective because SE focuses on resources rather than problems (23,25,42). In pain research, studies have shown that a high level of SE may be characterized as a protective psychological resource, and related to several positive health outcomes, such as greater ability to cope with pain, better quality of life, and fewer somatic symptoms (22,43,44). Surprisingly, our analyses did not reveal a significant association between high SE and daily pain in any location of any form.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SE is a positive phenomenon, and it is particularly relevant from a health promotion perspective because SE focuses on resources rather than problems (23,25,42). In pain research, studies have shown that a high level of SE may be characterized as a protective psychological resource, and related to several positive health outcomes, such as greater ability to cope with pain, better quality of life, and fewer somatic symptoms (22,43,44). Surprisingly, our analyses did not reveal a significant association between high SE and daily pain in any location of any form.…”
Section: Discussionmentioning
confidence: 99%
“…A higher score denotes a higher level of SE. This scale has been shown to be reliable and valid, as indicated by a Cronbach's  between 0.75 and 0.90 (22,24,25).…”
Section: Explanatory Variablesmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies have shown that self-efficacy and self-esteem have a positive impact on both pain and HRQOL in adolescents [ 18 , 35 43 ]. Higher levels of self-efficacy and self-esteem may protect an adolescent from experiencing pain, it can help to positively adapt and cope with pain, and it is associated with higher levels of HRQOL despite having pain [ 18 , 22 , 38 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…These data suggest the idea that physical and cognitive wellbeing can affect other wellbeing dimensions, influencing them positively [32]. When Physical and Psychological Wellbeing increase, then Mood and Emotions, Self-Perception, and Autonomy do in the same way, with the understanding that these types of wellbeing affect the rest and the dimensions are positively related [33].…”
Section: Discussionmentioning
confidence: 78%